As práticas morais como meio de experiência formativa em Joseph Maria Puig - Jappe, Maira (2012)
This dissertation aims at understanding the role played by the concept of moral practices in the proposed moral education of Joseph Maria Puig, concerning the construction of moral personality. In it we defend the hypothesis that in its proposal the concept of moral practices occupies a central place as a means of training and experience that occurs in that demand the active participation of the learner in the process of moral formation. This hypothesis is articulated in three steps argumentative, starting with the exposure of the fundamental dimensions of the proposed Puig, following the resumption of matrices with sociological, philosophical and psychological concept of moral practices to then thematize the concept of moral practices as a means of experience formative and therefore construction of moral personality. The methodology used was nature literature, guided by a critical procedure, diereconstructive analytical about the selected texts